Clinical efficacy of azacytidine and venetoclax and prognostic impact of Tim-3 and galectin-9 in acute myeloid leukemia and high-risk myelodysplastic syndromes: A single-center real-life experience - Giudice, Valentina; Serio, Bianca; Ferrara, Idalucia; Manzo, Paola; Gorrese, Marisa; Pepe, Rita; Bertolini, Angela; D’Alto, Francesca; Verdesca, Francesco; Langella, Maddalena; Filippelli, Amelia; Selleri, Carmine (Frontiers in Pharmacology, 2022)
Treatment of acute myeloid leukemia (AML) and high-risk myelodysplastic syndromes (MDS) is difficult in older patients with comorbidities and high-risk disease factors. Venetoclax, the first-in-class Bcl-2 inhibitor, has proven efficacy and safety in combination with azacytidine for treatment of high-risk myeloid diseases. In this single-center real-life retrospective study, a total of 27 consecutive patients treated with azacytidine plus venetoclax were included, and clinical outcomes, hematological improvements, and biomarkers of responsiveness to therapy were compared to those observed in an historical cohort of 95 consecutive patients treated with azacytidine as single agent. Azacytidine plus venetoclax was effective and safe in older and frail AML and high-risk MDS patients, with median overall survival of 22.3 months, higher than that reported in phase III trial (14.7 months), and higher than that of historical cohort (5.94 months). Progression-free survival (PFS) was higher in patients treated with the drug combination compared to those treated with azacytidine as single agent (P = 0.0065). Clinical benefits might increase when azacytidine and venetoclax are administered as upfront therapy (P = 0.0500). We showed that Tim-3 expression could be a promising therapeutic target in refractory/relapsed patients, and galectin-9 a biomarker of responsiveness to therapy. Moreover, patients treated with azacytidine and venetoclax displayed a higher overall survival regardless the presence of negative prognostic markers at diagnosis (e.g., increased WT1 copies and/or normalized blast count). These encouraging results in a real-world setting supported efficacy and safety of azacytidine plus venetoclax as upfront therapy in AML and high-risk MDS, with clinical outcomes comparable to those of clinical trials when an appropriate venetoclax management with bone marrow assessment at every first, second, fourth, and eighth cycle and dose adjustments for toxicities are performed.